Research method for locative games - Andrade, Luiz Adolfo (MedieKultur: Journal of media and communication research, 2018)
This paper presents a methodology approach for locative games studies using as reference the actor-network theory. The hypothesis supports that actor-network theory could be useful because it focuses on agencies between humans and non-humans; by the same way, it provides useful categories to support the researcher in the description of an emerging phenomenon. Locative gaming is a fruitful experience to use concepts from actor-network theory because it is connected to many humans and non-humans actants. In the attempt to achieve a research method for locative games using actor-network theory, this study provides a description of some game sessions of Pokémon GO played in Copenhagen during the summer of 2017.